Analysis of the Insurance Claim Settlement Mechanism of PT. Pru Syariah Binjai Achievement - Ella Sri Wahyu Ningsih; Yusrizal Yusrizal (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
PT Pru Syariah Prestasi Binjai provides protection for the insured along with very long term investments that carry high risks. This is because in addition to the life insurance company as the insurer, there are risks that come from investments that are sensitive to the global crisis that cannot be ascertained when it will occur. This research is focused on the benefits and mechanisms of prudential insurance. The research method uses empirical normative, with descriptive research type. The approach to the problem in this research is a non-judicial case study approach, namely the study approach at PT Prudential Life Assurance in Binjai City by examining the implementation of life insurance agreements. The results showed that the prudential insurance claim mechanism went through the process specified in the policy and the claims section had been prepared. The Insured is required to fill out all the prescribed claim forms. If the insured has an accident/illness, prepare supporting documents (original receipts, medical records, laboratory results, police reports). Furthermore, in the event of death, the heirs submit a claim doctor's certificate/hospital and the company will validate all documents and the investment results. Then the funds are transferred to the account of the insured or the related heirs.